Demokrasi dan Kinerja Pers Indonesia - Ngurah Putra, I Gusti (Jurnal ILMU KOMUNIKASI, 2006)
Abstract: Mass media, especially, press have important rules in the democration process. There are three criteria to evaluate performance of the press. Press as a civic forum, it’s related to Habermas’s public sphere that there is space for citizen to discuss about public interest in the free condition. Press as a watch-dog, that it’s means press has to protec minority rights from malfuntion of majority power. Press as a mobilization agent, it’s medium to increase society involment in the politic process.